A benign cancer with malicious paraneoplastic syndromes. (12th September 2013) - Vogt, Alexander; Wang, Shuang; Ventour, Dale
Abstract : A 70-year-old retired general practitioner with known follicular lymphoma presented with ptosis, dysphagia and progressive weakness in his upper and lower limbs. Despite having positive antibodies for myasthenia gravis he did not respond to conventional treatment with pyridostigmine, immunoglobulins and steroids. After 1 week on a general ward, he required intensive care for non-invasive ventilation. On the intensive care unit, he developed a secondary paraneoplastic syndrome in the form of a syndrome of inappropriate antidiuretic hormone secretion and required a tracheostomy for ventilatory support. After 1 week of invasive ventilation and remaining fully conscious throughout, he declined further treatment and passed away.